ICOS DNA methylation regulates melanoma cell-intrinsic ICOS expression, is associated with melanoma differentiation, prognosis, and predicts response to immune checkpoint blockade - Damian J. Ralser; Emmanuelle Herr; Luka de Vos; Zsófi Kulcsár; Romina Zarbl; Niklas Klümper; Gerrit H. Gielen; Alexander Philippe Maas; Friederike Hoffmann; Jörn Dietrich; Pia Kuster; Alexander Mustea; et al. (Biomarker Research, 2023)
Abstract Background Inducible T cell costimulator ICOS is an emerging target in immuno-oncology. The aim of this study was to investigate the epigenetic regulation of ICOS in melanoma by DNA methylation. Methods We comprehensively investigate ICOS DNA methylation of specific CpG sites and expression pattern within the melanoma microenvironment with regard to immune correlates, differentiation, clinical outcomes, and immune checkpoint blockade (ICB) response. Results Our study revealed a sequence-contextual CpG methylation pattern consistent with an epigenetically regulated gene. We found a cell type-specific methylation pattern and locus-specific correlations and associations of CpG methylation with ICOS mRNA expression, immune infiltration, melanoma differentiation, prognosis, and response to ICB. High ICOS mRNA expression was identified as a surrogate for enriched immune cell infiltration and was associated with favorable overall survival (OS) in non-ICB-treated patients and predicted response and a prolonged progression-free survival (PFS) following ICB therapy initiation. ICOS hypomethylation, however, significantly correlated with poor OS in non-ICB patients but predicted higher response and prolonged PFS and OS in ICB-treated patients. Moreover, we observed cytoplasmic and sporadically nuclear tumor cell-intrinsic ICOS protein expression. Tumor cell-intrinsic ICOS protein and mRNA expression was inducible by pharmacological demethylation with decitabine. Conclusion Our study identified ICOS DNA methylation and mRNA expression as promising prognostic and predictive biomarkers for immunotherapy in melanoma and points towards a hitherto undescribed role of ICOS in tumor cells.